Effect of Ligands on Luminescent Properties of Rare Earth Europium Complexes. Issue 1 (24th July 2021) - Li, Qinyi; Tang, Peisong; Hou, Ruipeng; Zhou, Yifan; Chen, Haifen
Abstract: Using Eu2 O3 as the source of europium, anhydrous ethanol as the solvent system, methylene benzoyl (DBM), 2-thiophenyl trifluoroacetone (TTA), 1-(4-tert-butylphenyl)-3 -(4-methoxyphenyl) −1, 3-propanedione (Avobenzone) and 2, 4, 6-trimethylbenzoic acid (TMBA) as first ligands, triphenyl phosphine (TPPO) as second ligands, the four kinds complexes of europium(III) ternary rare earth have been successfully prepared by precipitation reaction. The samples were characterized by absolute quantum efficiency meter (DQE), fluorescence spectrum (FS), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetry differential scanning calorimetry(TG-DSC). The influence of first ligand change on fluorescence intensity, fluorescence quantum efficiency, color temperature, color coordinate and thermal stability of complexes were analyzed from the perspective of energy transfer, so as to explore the influence of the first ligand on fluorescence performance of europium complexes. The results showed that the fluorescence of Eu(TTA)3 TPPO was the strongest, while the fluorescence of Eu(TMBA)3 (TPPO) was the weakest.